WR 227 - Technical Writing - Linn Benton Virtual College (2018)
This course introduces students to the types of writing they will encounter in business, industry, the academic world and government. It examines the rhetorical nature of writing and asks students to think critically about content, audience, argument and structure. Students will learn how to effectively design documents, present instructions, create proposals and produce technical reports.